2007
DOI: 10.1038/sj.jp.7211848
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal suctioning is associated with prolonged disturbances of cerebral hemodynamics in very low birth weight infants

Abstract: Objectives: Examining the effects of tracheal suctioning on cerebral hemodynamics of normotensive ventilated very low birth weight (VLBW) infants with normal cranial ultrasounds; determining the factor(s) influencing changes in mean cerebral blood flow velocity (CBFv) after suctioning.Methods: Seventy-three VLBW infants had continuous monitoring of mean arterial blood pressure (MABP), PaCO 2 , PaO 2 and mean CBFv before, during, and after 202 suctioning sessions during the first week of life. Peak (or nadir) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 36 publications
2
30
0
1
Order By: Relevance
“…As suctioning spontaneously breathing newborns is not beneficial and may even be harmful, nasoor oropharyngeal suctioning is only recommended if the mouth and nose are visibly obstructed by secretions or meconium [19] . Suctioning is reported to be associated with an increased risk of intraventricular hemorrhage, apnea, vagal reflex bradycardia, and delayed resuscitation [20,21] . Despite these recommendations, airway suctioning was performed in 5% of the newborn infants.…”
Section: Discussionmentioning
confidence: 99%
“…As suctioning spontaneously breathing newborns is not beneficial and may even be harmful, nasoor oropharyngeal suctioning is only recommended if the mouth and nose are visibly obstructed by secretions or meconium [19] . Suctioning is reported to be associated with an increased risk of intraventricular hemorrhage, apnea, vagal reflex bradycardia, and delayed resuscitation [20,21] . Despite these recommendations, airway suctioning was performed in 5% of the newborn infants.…”
Section: Discussionmentioning
confidence: 99%
“…3,15,[25][26][27] In the prior studies, cerebral autoregulation was found to be influenced by hypercapnia and associated with severe IVH. In addition, changes to cerebral hemodynamics occurred during surfactant administration and tracheal suctioning.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, physical factors that can change these two parameters can affect CBF. Moderate changes in the mean arterial blood pressure (MABP) have not been found to cause significant changes in CBF of infants with intact cerebral autoregulation [9]. If abrupt changes in the MABP are prevented, and in the absence of hypoglycemia and anemia that can increase CBF, the most important factors affecting the CBF of mechanically ventilated infants with intact CBF autoregulation are considered to be the arterial partial pressures of carbon dioxide and oxygen [7][8][9].…”
Section: Introductionmentioning
confidence: 99%